State-of-the-Art of the Nutritional Alternatives to the Use of Antibiotics in Humans and Monogastric Animals - Saettone, Vittorio (Animals (Basel), 2020)
SIMPLE SUMMARY: Antibiotic resistance represents a worldwide recognized issue affecting both human and veterinary medicine, with a particular focus being directed towards monogastric animals destined for human consumption. This scenario is the result of frequent utilization of the antibiotics either for therapeutic purposes (humans and animals) or as growth promoters (farmed animals). Therefore, the search for nutritional alternatives has progressively been the object of significant efforts by the scientific community. So far, probiotics, prebiotics and postbiotics are considered the most promising products, as they are capable of preventing or treating gastrointestinal diseases as well as restoring a eubiosis condition after antibiotic-induced dysbiosis development. This review provides an updated state-of-the-art of these nutritional alternatives in both humans and monogastric animals. ABSTRACT: In recent years, the indiscriminate use of antibiotics has been perpetrated across human medicine, animals destined for zootechnical productions and companion animals. Apart from increasing the resistance rate of numerous microorganisms and generating multi-drug resistance (MDR), the nonrational administration of antibiotics causes sudden changes in the structure of the intestinal microbiota such as dysbiotic phenomena that can have a great clinical significance for both humans and animals. The aim of this review is to describe the state-of-the-art of alternative therapies to the use of antibiotics and their effectiveness in humans and monogastric animals (poultry, pigs, fish, rabbits, dogs and cats). In particular, those molecules (probiotics, prebiotics and postbiotics) which have a direct function on the gastrointestinal health are herein critically analysed in the prevention or treatment of gastrointestinal diseases or dysbiosis induced by the consumption of antibiotics.